2021
DOI: 10.31234/osf.io/659yd
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Worker well-being before and during the COVID-19 restrictions: A longitudinal study in the UK

Abstract: The potential impact of COVID-19 restrictions on worker well-being is currently unknown. In this study we examine 15 well-being outcomes collected from 621 full-time workers assessed before (November, 2019 - February, 2020) and during (May-June, 2020) the COVID-19 pandemic. Fixed effects analyses are used to investigate how the COVID-19 restrictions and involuntary homeworking affect well-being and job performance. The majority of worker well-being measures are not adversely affected. Homeworkers feel more en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…At the same time, some have heralded the COVID-19 pandemic as a catalyst for better work-life balance, particularly for individuals with good job security and flexible employment and family responsibilities. In addition to these opposing anecdotal discussions, empirical work has been similarly mixed, with some research observing well-being decrements among individuals 2,3 and others reporting well-being stability or improvements over time or as a function of other factors 4,5,6 . Although some studies (reviewed more later) have involved data collected over time, much of this research has been crosssectional in nature 7,8 , only producing "snapshots" of worker well-being at isolated time points.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, some have heralded the COVID-19 pandemic as a catalyst for better work-life balance, particularly for individuals with good job security and flexible employment and family responsibilities. In addition to these opposing anecdotal discussions, empirical work has been similarly mixed, with some research observing well-being decrements among individuals 2,3 and others reporting well-being stability or improvements over time or as a function of other factors 4,5,6 . Although some studies (reviewed more later) have involved data collected over time, much of this research has been crosssectional in nature 7,8 , only producing "snapshots" of worker well-being at isolated time points.…”
Section: Introductionmentioning
confidence: 99%
“…Those individuals experienced fewer negative emotions and felt more connected to their organization. However, their home-life satisfaction and job performance according to their own evaluations decreased (Pelly, Daly, & Delaney, 2021).…”
Section: The Effect Of Covid-19 On Happiness Economic Socioeconomic A...mentioning
confidence: 96%
“…The fall in subjective well-being due to the context has been abundantly documented (e.g. Anaya et al, 2021;Banks & Xu, 2020;Brodeur et al, 2021;Pelly et al, 2021;Pierce et al, 2020;Schmidtke et al, 2021;Sibley et al, 2020), but while in the early days of the lockdown, increased symptoms of depression and anxiety were often attributed to telecommuting, with the easing of restrictions, many surveys revealed that the vast majority of workers do not want to return to the office 5 days a week. Aksoy et al (2022), for instance, ran a global survey of working arrangement in 27 countries and found that both employers and employees expect to see WFH continue after the pandemic.…”
Section: Previous Studiesmentioning
confidence: 99%